DIFFERENCE IN URIC ACID TEST RESULTS USING PLAIN AND CLOT ACTIVATOR VACUTAINER TUBES - Permana, Anak Agung Gede Denny Dwi; Cahyani, Anak Agung Ayu Eka; Yanti, Ni Luh Gede Puspita (PT. Jurnal Center Indonesia Publisher, 2025)
Laboratory examinations play an important role in supporting disease diagnosis and treatment, one of which is the measurement of uric acid levels. The accuracy of laboratory results is significantly influenced by the pre-analytical stage, including the type of blood collection tube used. Two commonly used tubes are the plain vacutainer and the clot activator vacutainer, each with different additives that may affect blood clotting time and test results. This study aimed to determine the differences in uric acid test results and clotting time using these two types of tubes. A simple experimental method with a comparative design was conducted at Klinik Pratama Rawat Jalan Mambal Medical Care from March to April 2025. The sample consisted of 15 respondents, each undergoing two blood draws using both tube types. The results showed that the average clotting time for the clot activator tube was 9.27 minutes, while for the plain tube it was 24.67 minutes. The average uric acid level measured using the clot activator tube was 5.27 mg/dL, compared to 5.14 mg/dL using the plain tube. Statistical analysis using the Wilcoxon signed-rank test indicated a significant difference in clotting time but no significant difference in uric acid levels (p > 0.05). It can be concluded that the use of clot activator vacutainer tubes accelerates the blood clotting process but does not significantly affect uric acid levels compared to plain tubes.